(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
This study presents the suitability of mashed periwinkle shell (MPS) as fine aggregate on concrete compressive strength for disaster mitigation. The effect of mashed periwinkle shell (MPS) at 0%, 10%, 20%, 50% and 100% replacement as fine aggregate was investigated for its concrete compressive strength. Laboratory and non-linear regression mathematical model methods were adopted in this study. Preliminary tests like sieve analysis, specific gravity etc. were performed on the aggregate materials from which a mix ratio of 1:2:4 was obtained. A total of 60 concrete cubes of 150 mm x 150 mm x 150 mm sizes were cast, properly cured and checked for the 7, 14, 21, 28 days compressive strength. The results obtained showed optimum improvement on concrete compressive strength at 10% and 20% MPS replacement as fine aggregate for both the experimental and model methods. The 100% MPS replacement gave a poor strength gain showing that MPS full replacement as sand in concrete might cause failure of the structure. The mathematical model gave a better representation of the concrete strength and the accuracy of the model determined from results of the coefficient of determination gotten as; 0.980, 0.97, 0.986 and 0.989 respectively. Hence this study tends to mitigate against using sub-standard materials in construction and also solves environmental problems that might arise from dumping periwinkle shells.